Population genetic analyses highlight an eastward dispersal of Puccinia striiformis f. sp. tritici from the Shaanxi province to the North China Plain - Congying Zhou; Xuan Lv; Xinlei Qi; Ahsan Abdullah; Qiuyu Sun; Mingliang Ding; Yingwen Bai; Ziqian Yang; Zhifang Wang; Zhanhong Ma (Phytopathology Research, 2024)
Abstract Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a common airborne wheat disease. The frequent occurrence at a large scale in China has caused significant yield losses and poses a considerable threat to food security. To effectively manage and forecast the disease, a comprehensive understanding of the long-distance migration patterns of Pst is essential. Shaanxi province, situated in close proximity to the northwestern epidemic areas in China, plays a crucial role as a key overwintering region for Pst. However, it remains uncertain whether Pst, after winter reproduction in Shaanxi province, can extend its spread to the primary wheat regions in the North China Plain. In this study, during February and June 2022, a total of 302 Pst samples were collected from Shaanxi province and the North China Plain. Thirteen pairs of simple sequence repeat (SSR) markers were adopted to analyze the population genetic structure. It was observed that both genetic and genotypic diversities exhibited a discernible decline from the Shaanxi to the North China Plain. Moreover, Shaanxi displayed a close genetic relationship with Henan and Shandong, whereas Henan exhibited the most substantial population exchange with Shaanxi. Further analysis revealed that Shaanxi served as the primary inoculum of Pst in the investigated region, and the spread of Pst to Henan and Shandong originated from Shaanxi. As a result, the epidemics in Shandong further led to the prevailing of the disease in Hebei. Our study enhances the understanding of the epidemiological patterns of wheat stripe rust in the springtime prevalent regions of China, and it provides insights for future disease management.